Investigating the physical elements that promote vitality and encourage sense of community in public markets - Baldovino, Stephanie Gwen N. (2023)
Public markets, being bustling hubs of trade and human interaction, hold significant importance as public spaces. This study tried to investigate the physical attributes found in public markets that promote vitality and also encourage the formation of sense of community. This study emphasizes the vitality of these markets because it is a key aspect of urban quality. Parameters such as Attractiveness, Accessibility, Maintenance, Safety and Security, Inclusiveness, and Enjoyment were used to measure market vitality. Sense of community is investigated because it is crucial for public places such as markets to be areas for developing social well-being of the public. Sense of community was evaluated using McMillan and Chavis' four elements: Membership, Influence, Fulfillment, and Shared Emotional Connections. Data was collected through surveys, observation, documentation, and interviews, and analyzed using various methods. The results indicate positive correlations between Attractiveness, Accessibility, Maintenance, Safety and Security, Inclusiveness, and Enjoyment with the improvement of the market goers' sense of community. Similarly, Attractiveness and Maintenance were positively correlated with the vendors' sense of community. Market goers who perceive the market as safe, accessible, inclusive, well-maintained, attractive, and enjoyable tend to have a stronger sense of community, resulting in increased participation and well-being. For vendors, a focus on attractiveness and good maintenance of their areas fosters a stronger sense of community. Open spaces with minimal stall partitions and clutter were associated with high scores in these variables. Enhancing these elements in public market design promotes community cohesion. Additionally, providing areas for extended stays and facilitating direct access to different sections of the market encourages casual interactions among market goers, reinforcing their sense of community. Vendors benefit from designing their stalls and areas to be more exposed to open spaces and people, thus strengthening their sense of community.